Early Postoperative Complications After Coronary Artery Bypass Grafting at the San Juan Veterans Affairs Medical Center - Escabí-Mendoza, José; Acevedo, José; Rucabado, Elena; Pérez, Cynthia M.; Rodríguez-Ospina, Luis (Puerto Rico Health Sciences Journal, 2005)
see manuscript